“THEY SURROUNDED AND CAPTURED HIM LIKE WOLVES THAT CAPTURE A SHEEP”. JEWS IN THE LATE MEDIEVAL POLISH APOCRYPHA: ROZMYŚLANIA DOMINIKAŃSKIE, ROZMYŚLANIE PRZEMYSKIE, AND SPRAWA CHĘDOGA O MĘCE PANA CHRYSTUSOWEJ - Vincůrková, Dorota (Prace Polonistyczne, 2021)
The article analyses the construction of Jewish characters in the following late medieval Polish apocrypha: Rozmyślania dominikańskie, Rozmyślanie przemyskie, and Sprawa chędoga o męce Pana Chrystusowej. The characters are built on a contrast between the figure of Christ and his tormentors. The article studies the following aspects of the contrast: hyperbolized aggression, beastial imagery, and the impurity of the perpetrators (which is conspicuous in images originating from the humoral theories). The literary representation of Jews (rather than Roman soldiers) as the ‘physical’ culprits of the Crucifixion of the Saviour also plays an important role in the texts under discussion